Pengaruh Kinerja Pegawai terhadap Kualitas Pelayanan Bank BRI Unit Wayame - Helnida Wati Telaumbanua; Normawati Normawati; La Madjid (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the influence of employee performance on service quality at Bank Rakyat Indonesia (BRI) Unit Wayame, Ambon City. The research is grounded in recurring customer complaints related to service delays, limited operational service time, unclear queue management, and perceived responsiveness gaps in front-line banking services. A quantitative associative design was employed with 40 customers selected through accidental sampling. Data were collected using a Likert-scale questionnaire measuring employee performance and service quality, then analyzed using validity testing, reliability testing, descriptive statistics, and simple linear regression. The results show that employee performance has a positive and significant effect on service quality. The regression equation is Y = 9.485 + 0.784X, with a t-value of 7.679 and a significance level below 0.001. The coefficient of determination indicates that employee performance explains 60.8% of the variation in service quality. These findings imply that accuracy, punctuality, responsibility, teamwork, and employee initiative are central factors in improving customer perceptions of banking services. Strengthening training, supervision, communication capacity, and internal performance evaluation is therefore essential to improve service quality at the unit level.